Frequency of Hyponatremia in Tuberculous Meningitis Patients - ftikhar Ali Kakar, Nasir Azim, Abdul Baqi, Kiran Ghafoor, Nimra Hayat, Khalid Shahab, Muhammad Idrees, Hira Qamar, (Pakistan Journal of Medical & Health Sciences, 2023)
Back Ground: A severe inflammation of the meninges is often referred to as meningitis. Hyponatremia has been associated with tuberculous meningitis in numerous studies. Objective: To assess the frequency of hyponatremia in tuberculous meningitis patients Methodology: This cross sectional study was carried out at the department of Neurology Bolan Medical Complex Hospital, Fatima Jinnah Institute of Chest Diseases and Sheikh Khalifa Bin Zayyed Al Nahyan Medical Complex Quetta for duration of one year from September 2021 to September 2022. All the required data like name, gender and presence or absence of hyponatremia were documented in a special proforma designed for this research. Data analysis was carried out by using SPSS version 23. Results: In our study, totally 210 patients were included. The male participants in our study were 94 (44.76%) while female participants were 116 (55.24%). The mean sodium level in serum was observed to be 133 with SD of ± 4.29. The overall frequency of hyponatremia in tuberculous meningitis patients was 113 (53.81%). Conclusion: Our study concludes that the frequency of hyponatremia in tuberculous meningitis patients was very high (53.81%). Hyponatremia may have serious implications, including serious neurological problems and death, if it is not properly diagnosed and treated early Keywords: Frequency, hyponatremia, tuberculous meningitis